Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper discusses the fiscal policy in the Korean business cycle, and examines the usefulness of the equations for inflation forecasting at horizons consistent with the Bank of Korea 's inflation-targeting framework. It analyzes the causes and macroeconomic consequences of Korea's dual labor market; discusses the government's reform proposals; and the nonbank financial sector restructuring to date.